Coping styles and the extent of change in gender roles of wives and husbands of overseas contract workers in Miagao and Guimbal town proper. - Gernade, Lynnie Ann P.
This study sought to find out if there are significant differences in coping styles and extent of change in gender roles between wives and husbands of Overseas Contract Workers. Moreover, this study aimed to examine if there is a relationship between coping styles and the extent of change in gender roles. Using stratified random sampling, thirty females and thirty males were selected as the respondents. Data was gathered using two sets of questionnaires. The Coping Style Scale was used to measure coping styles and the Evolving Gender Role Scale was used to measure the extent of change in gender roles. With the use of t-test, it was found out that no significant difference exists in coping styles and in the extent of change in gender roles between wives and husbands of migrant workers. With the use of Pearson Product-Moment Correlation, it was found out that there is a low correlation between coping styles and extent of change in gender roles.